Fathers' involvement in the child's early education - Reyes, Kristine Marie T.; Dy, Marison R. (2011)
The study explored the willingness of fathers of preschoolers to be involved in the preschool activities of their child, their actual involvement, and the factors which facilitated/hindered their involvement. There were 36 father-respondents from the Child Development Laboratory (CDL) who were administered an interview schedule. They were residents of Los Banos, Laguna and nearby towns, and aged 23-54 years old.

The findings of the study showed that majority of the respondents (92%) were willing to be involved in some preschool activities designed for parent involvement. Of this group. some 28% reported they were highly willing to be involved with a level of willingness at 10, the highest level.

The nature of involvement most of them wanted was as a Teacher Daddy or resource person, game master, or storyteller to the class of their children. The respondents wanted to be involved because they felt that fathers should be involved in their child's schooling and that with the involvement, they will be able to strengthen the father-child relationship, share their knowledge about their occupation, develop in their child a sense of pride in their profession, and simply have an enjoyable time with their child and the whole class.

High ratings for willingness however, do not necessarily translate to behavior since there were intervening factors like conflicts in their work schedule or demands in their occupations. Thus, only eight percent became actually involved in their chosen nature of participation in the preschool within the school year. For further studies, it is recommended that a more diverse sample of fathers from public and private preschools programs be included.
Keywords: Preschool education -- Parent participation